2016
DOI: 10.3390/md14050093
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Oxidative Activity of Mytiloxanthin, a Metabolite of Fucoxanthin in Shellfish and Tunicates

Abstract: Anti-oxidative activities of mytiloxanthin, a metabolite of fucoxanthin in shellfish and tunicates, were investigated. Mytiloxanthin showed almost the same activities for quenching singlet oxygen and the inhibition of lipid peroxidation as those of astaxanthin, which is a well-known singlet oxygen quencher. Furthermore, mytiloxanthin showed excellent scavenging activity for hydroxyl radicals and this activity was markedly higher than that of astaxanthin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Through this metabolic conversion, antioxidative activities such as singlet oxygen quenching, scavenging of hydroxy radicals, and inhibition of lipid peroxidation of carotenoids are increased. Mytiloxanthin showed almost the same excellent antioxidative activity as that of astaxanthin [13]. Therefore, it was concluded that marine animals metabolize dietary carotenoids to a more active antioxidative form and accumulate them in their bodies and reproductive organs.…”
Section: Biological Function Of Carotenoids In Marine Animalsmentioning
confidence: 97%
“…Through this metabolic conversion, antioxidative activities such as singlet oxygen quenching, scavenging of hydroxy radicals, and inhibition of lipid peroxidation of carotenoids are increased. Mytiloxanthin showed almost the same excellent antioxidative activity as that of astaxanthin [13]. Therefore, it was concluded that marine animals metabolize dietary carotenoids to a more active antioxidative form and accumulate them in their bodies and reproductive organs.…”
Section: Biological Function Of Carotenoids In Marine Animalsmentioning
confidence: 97%
“…Takashi Maoka et al. synthesized mytiloxanthin and studied its anti‐oxidative activities and found that the compound showed excellent scavenging activity for hydroxyl radicals . Caroline Utermann et al.…”
Section: Marine Animal Sourcesmentioning
confidence: 99%
“…[22] Takashi Maoka et al synthesized mytiloxanthin and studied its anti-oxidative activities and found that the compound showed excellent scavenging activity for hydroxyl radicals. [23] Caroline Utermann et al isolated an Alloxanthin analogue (8) from mussels (Mytilus spp.) collected at an organic blue mussel farm located in KF (Baltic Sea, Germany).…”
Section: Carotenoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Carotenoid composition in muscle of Halocynthia aurantium and H. roretzi ka et al34) は mytiloxanthin が astaxanthin とほぼ同等の 一重項酸素消去活性および脂質過酸化抑制活性を示すこ とを,Narita et al 35) は pectenolone が astaxanthin とほ Suzuki Y. Biochemical studies of the ascidian, Cynthia roretzi v. drasche-VIII. On the general components.…”
mentioning
confidence: 99%